Adesão ao fascismo e preconceitos contra negros: um estudo com universitários na cidade de São Paulo - Galeão-Silva, Luis Guilherme (2007)
Recently, Brazilian society has experienced a shift in the perception of racial inequality. Few years ago, it was widely spread the notion that there was no racism in Brazil and that the social conditions were the main problem of black population. Nowadays, however, it seems that the majority of Brazilians has realized there is, indeed, racism in Brazil. The nature of racial prejudice against black people raises many questions. Here we had proposed to explore one of these questions: the relationship between subtle prejudice, explicit prejudice and tendency to Fascism. We hypothesized that subtle and explicit prejudice against black people are correlated to a tendency to Fascism. To investigate this hypothesis, it was applied a questionnaire to 103 students of a Business Administration School, who self-declared being white. It was performed a critical social research. The questionnaire was composed by the F-scale (Fascism) blatant prejudice and subtle prejudice. In our results it was found a correlation between F-scale and both types of prejudice. In addition, we found a higher mean in the F-scale, subtle prejudice and blatant prejudice, respectively. The most relevant correlation occurred between F-scale and subtle prejudice. We interpreted that students with subtle prejudice against black people have higher tendency to Fascism. It was done a factor analyses with the principal factor method. We concluded from the correlation and the data analysis that the subtle prejudice signalizes similarities between psychological conditions and adhesion to Fascism and the contemporary racist ideology. We suggested that the need of social measures for black and white people should be followed by a critic perspective and by changes of social conditions that lead to authoritarianism